Two New Species of Laccaria (Agaricales, Basidiomycota) from Korea - Cho, Hae Jin; Lee, Hyun; Park, Myung Soo; Park, Ki Hyeong; Park, Ji Hyun; Cho, Yoonhee; Kim, Changmu; Lim, Young Woon (Mycobiology, 2020)
Species of Laccaria (Hydnangiaceae, Agaricales, and Basidiomycota) are well-known ectomycorrhizal symbionts of a broad range of hosts. Laccaria species are characterized by brown, orange, or purple colored basidiocarps, and globose or oblong, echinulate and multinucleate basidiospores. While some Laccaria species are easily identified at the species level using only the morphological characteristics, others are hard to distinguish at the species level due to small differences in morphology. Heretofore, ten Laccaria species have been reported in Korea. While studying the fungal diversity in the National Parks of Korea, two new Laccaria species were discovered. Species identification was done based on molecular analyses (ITS, 28S rDNA, rpb2, and tef1), then were confirmed by their corresponding morphologies. The two newly discovered Laccaria species are proposed here as Laccaria macrobasidia and Laccaria griseolilacina. The unique morphological characters of L. macrobasidia that distinguish it from its closely related species are orange-brown colored basidiocarp, long basidia and the absence of cheilocystidia. L. griseolilacina is characterized by a light grayish lavender-colored pileus and the absence of cheilocystidia. Two new species are described and illustrated in the present paper.